1995
DOI: 10.1113/jphysiol.1995.sp020821
|View full text |Cite
|
Sign up to set email alerts
|

Action potential generation in rat slow‐ and fast‐twitch muscles.

Abstract: 1. In skeletal muscle fibres, voltage-gated sodium channels are concentrated at the neuromuscular junction. The effect of this accumulation of sodium channels on action potential generation was investigated in rat slow-and fast-twitch muscle fibres. 2. Intracellular microelectrodes were used to generate and record action potentials, from an imposed membrane potential of -75 and -90 mV, in junctional and extrajunctional regions of the muscle fibre. To identify junctional regions, preparations were incubated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 34 publications
(61 reference statements)
3
43
0
Order By: Relevance
“…In both cell types, AP threshold and overshoot were comparable to those reported for cultured human primary myotubes from muscle biopsies (18,21), and for mammalian skeletal muscle, in general (22). AP kinetics vary with experimental conditions (temperature, protocols, etc.)…”
Section: Discussionsupporting
confidence: 75%
“…In both cell types, AP threshold and overshoot were comparable to those reported for cultured human primary myotubes from muscle biopsies (18,21), and for mammalian skeletal muscle, in general (22). AP kinetics vary with experimental conditions (temperature, protocols, etc.)…”
Section: Discussionsupporting
confidence: 75%
“…allowing quantal analyses to be acquired directly from recordings of endplate currents obtained using a two-electrode voltage clamp [41]). Wood & Slater [53,54] measured safety factor in this fashion by comparing the observed endplate current with that required to critically depolarize muscle fibres to the action potential firing threshold. They concluded that, once differences in the contribution of post-synaptic junctional folding were taken into account, the safety factor in rat soleus (a slow-twitch muscle) corresponded to about 3.5 times as much neurotransmitter released at an NMJ over the requirement to trigger muscle action potentials; but this was significantly lower than at NMJs in extensor digitorum longus (a fast-twitch muscle), where the safety factor was about 5.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the structure and molecular organization of the postsynaptic apparatus takes an excess of the released transmitter from the nerve, helping to ensure that every nerve impulse normally triggers a muscle action potential with a very small chance of failure. The concept of safety factor for neuromuscular transmission describes this excess (Martin, 1994;Wood and Slater, 1995, 1997, 2001. It is of interest that a modest reduction of rapsyn expression already causes substantial changes, showing that the amount of rapsyn is critically related to the AChR levels and to the structure of the endplate.…”
Section: Discussionmentioning
confidence: 99%